Literature Study: Potential of 3D Printing Technology in the World of Mechanical Engineering and Manufacturing - Santoso, Ari Beni; Saputra, Rahmad Surya Hadi (Journal of Renewable Engineering, 2025)
This study discusses the paradigm shift in mechanical engineering due to the adoption of 3D printing technology as part of the industrial revolution 4.0. This additive manufacturing technology offers advantages in terms of design complexity, production efficiency, and cost flexibility, but also raises technical challenges such as material anisotropy, surface roughness, and process parameter control. Through a descriptive qualitative approach based on literature studies, this study explores the impact of 3D printing on the structure of the manufacturing industry, performance-based design, and the need for reform in engineering education. Data sources are taken from scientific journals, academic books, and technical reports from the last decade (2014–2024), with a thematic analysis of technology applications, implementation challenges, and implications for mechanical engineering curricula. The results show that although 3D printing has fundamentally changed the design and production process, its integration into the industry is still limited by conventional supply chain structures and lack of human resource readiness. This study emphasizes the importance of transforming the engineering education system towards a digital-based interdisciplinary approach, as well as the need for critical and contextual technology adoption. Thus, 3D printing does not only act as a production tool, but also as a catalyst for systemic change in mechanical engineering and manufacturing.